Metabolites characterisation of laccase mediated Reactive Black 5 biodegradation by fast growing ascomycete fungus Trichoderma atroviride F03 - Liyana Amalina Adnan; Palanivel Sathishkumar; Abdull Rahim Mohd Yusoff; Tony Hadibarata (Elsevier, 2024)
In this study, fast growing ascomycete fungus Trichoderma atroviride F03 was explored to biodegrade bis-azo dye, Reactive Black 5 (RB5). The maximum RB5 biodegradation (91.1%) was achieved in the culture medium supplemented with an appropriate carbon source (glucose, 20 g l−1), and nitrogen source (yeast extract, 20 g l−1) at pH 5 and 27 °C. The laccase produced by T. atroviride F03 was involved in the RB5 biodegradation processes. The metabolites such as (I) 1,2,4-trimethylbenzene, (II) 2,4-ditertbutylphenol, and (III) benzoic acid-TMS) were identified as the biodegradation products of RB5 using gas chromatography-mass spectrometry (GC–MS). The presence of these metabolites suggested that RB5 biodegradation was initiated by the cleavage of azo bond forming naphthalene-1,2,8-triol and sulphuric acid mono-[2-(toluene-4-sulfonyl)-ethyl] ester. The sulphuric acid mono-[2-(toluene-4-sulfonyl)-ethyl] ester was further desulphonated to 1,2,4-trimethylbenzene. Then, the oxygenated ring of C1 and C2 naphthalene-1,2,8-triol was cleaved to 2-(2-carboxy-ethyl)-6-hydroxy-benzoic acid. The degradation of 2-(2-carboxy-ethyl)-6-hydroxy-benzoic acid could be proceeded with two pathways: (i) decarboxylation and methylation to form 2,4-ditertbutylphenol and (ii) decarboxylation mechanism that induced the formation of benzoic acid-TMS. Finally, this study proved that T. atroviride F03 might be a good candidate in treating textile effluent containing azo dye as this treatment does not generating aromatic amines.